The Czech Republic's 2022 Report Card on Physical Activity for Children and Youth: A rationale and comprehensive analysis - Gába, Aleš; Baďura, Petr; Vorlíček, Michal; Dygrýn, Jan; Hamřík, Zdeněk; Kudláček, Michal; Rubín, Lukáš; Sigmund, Erik; Sigmundová, Dagmar; Vašíčková, Jana (Journal of exercise science and fitness, 2022)
BACKGROUND/OBJECTIVE: The second edition of the Czech Republic's Report Card on Physical Activity for Children and Youth was released in 2022. This paper describes the development of the Report Card and presents a comprehensive summary of the main findings. METHODS: The multi-level search strategy was developed by the national expert panel to identify the available sources that provide data related to the physical activity of Czech children and adolescents. The data were used to assign grades to ten core and two additional indicators. RESULTS: A total of 28 sources provided data that allowed grades to be assigned to 11 out of the 12 indicators. Grade B was assigned to six indicators (School: B+, Community and Environment: B, Organized Sport and Physical Activity: B-, Active Transportation: B-, Family and Peers: B-, Sleep: B-), grade C to three indicators (Overall Physical Activity: C+, Active Play: C, Physical Literacy: C), and grade D to two indicators (Government: D+, Sedentary Behaviors: D). No grade for the "Physical Fitness" indicator could be assigned due to a lack of data collected in the reference period 2018-2019. CONCLUSIONS: Although the family, school, and built environment provided a variety of opportunities to be physically active, a high proportion of children and adolescents did not meet the current physical activity guideline and were exposed to excessive sedentary behavior. A multisectoral and multidisciplinary response is required to reduce the health and economic burden of physical inactivity and excessive sedentary behavior among Czech children and adolescents.
Keywords: Sleep; Environmental determinants; Sports; Social determinants; Sedentary behavior; Physical fitness